2015
DOI: 10.1302/0301-620x.97b4.33740
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic nature of alignment and variations in normal knees

Abstract: The restoration of knee alignment is an important goal during total knee arthroplasty (TKA). In the past surgeons aimed to restore neutral limb alignment during surgery. However, previous studies have demonstrated alignment to be dynamic, varying depending on the position of the limb and the degree of weight-bearing, and between patients. We used a validated computer navigation system to measure the femorotibial mechanical angle (FTMA) in 264 knees in 77 male and 55 female healthy volunteers aged 18 to 35 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…The situation is further complicated by differences in the alignment of the limb when measured in a lying position (which is non-weight bearing) and in a weight-bearing standing position[16]. In a study by Deep et al[17], they found the limb alignment to be dynamic process that differs according to different postures, and also varies between males and females in normal knees. Deep et al[17] found also a greater tendency into varus malalignment in the study group with normal non-arthritic knees, that go into more varus when changing the position from supine to standing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation is further complicated by differences in the alignment of the limb when measured in a lying position (which is non-weight bearing) and in a weight-bearing standing position[16]. In a study by Deep et al[17], they found the limb alignment to be dynamic process that differs according to different postures, and also varies between males and females in normal knees. Deep et al[17] found also a greater tendency into varus malalignment in the study group with normal non-arthritic knees, that go into more varus when changing the position from supine to standing.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Deep et al[17], they found the limb alignment to be dynamic process that differs according to different postures, and also varies between males and females in normal knees. Deep et al[17] found also a greater tendency into varus malalignment in the study group with normal non-arthritic knees, that go into more varus when changing the position from supine to standing. Walcox et al[16] found similar changes in arthritic knees.…”
Section: Discussionmentioning
confidence: 99%
“…The IR technology used in this study provided a real-time kinematic dynamic measurement of the FTMA, resulting in a powerful tool for intraoperatively supporting and guiding the surgeon in a very demanding challenge, such as the adequate postoperative balance of the knee. 6,[32][33][34][35] A change in coronal alignment between standing and supine positions has been previously demonstrated in normal, osteoarthritic, and postoperative knees. 6,7 Patients who are in varus or up to 2.5 degrees valgus while supine, tend to become more varus on standing.…”
Section: Discussionmentioning
confidence: 81%
“…6,[32][33][34][35] A change in coronal alignment between standing and supine positions has been previously demonstrated in normal, osteoarthritic, and postoperative knees. 6,7 Patients who are in varus or up to 2.5 degrees valgus while supine, tend to become more varus on standing. 6 This trend is also observed in a flexed position when compared with hyperextending.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation